Focus points of health tourism in the view point of changing costumer values - Lehota, József; Manuel, Tiago; Rácz, Georgina (Applied Studies in Agribusiness and Commerce, 2014)
In our study, effecting role of values on consumer’s buying decisions is going to be introduced in accordance with health tourism. Investigation of values has a highlighted role to predict future trends, because trends of consumer behavior are formed by values in several aspects. Furthermore, individual values reflect to subject’s lifestyle, purchasing behavior and decisions in connection with free time activities. Since the end of ‘80s results of social studies pointed out that, status fortifying and demonstrative aspect of consumption have been getting stronger. So, the changes of buying decisions are not based on the social stratums any more, but it represents the values of the individual with the growing effect of subject. Hence, values, expressing the subjective judgments of consumers, are the most precise predictors of long term social changes. In our study mainstreams of health tourism are going to be evaluated on the basis of secondary data. Furthermore, we identify place of health among individual values and its role in consumer decisions. During the analysis, we use data of national representative research to determine the Hungarian society’s opinion and judgments in the viewpoint of health. Uni- and multivariate statistical methods are going to be used to get a wide view in accordance with the investigated topic. Among our most important result, we define those consumer groups, in which health has a highlighted role in consumer decisions. We introduce lifestyle characters of these segments and determine them special needs in connection with purchased goods and services. This type of characterization makes it real to organizations of health tourism to develop a more effective marketing communication strategy and improve service features according to consumer needs.